2013
DOI: 10.1111/jfbc.12048
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibitory Potential Against Key Enzymes Relevant for Hyperglycemia and Hypertension of Red Pepper (Capsicum annuum L.) Including Pericarp, Placenta, and Stalk

Abstract: Extracts from the pericarp, placenta and stalk of red pepper (Capsicum annuum L) were investigated to determine their antioxidant and in vitro inhibitory potential against key enzymes relevant for hyperglycemia and hypertension. We examined the total phenolic and capsaicin content in red pepper extract. Anti-hyperglycemia relevant in vitro α-glucosidase inhibitory activity correlated strongly to the antioxidant activity measured by the 1, 1-diphenyl-2-picrylhydrazyl method. The high phenolic and capsaicin cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Aliakbarlu et al [32] found that TPC in red pepper was 34 mg GAE/g DW. Chen and Kang [33] observed that TPC of red peppers in pericarp, placenta and stalk were ranged from 43.3 to 91.9 mg GAE/g DW. Finally, Nascimento et al [34] revealed that total phenolic contents of Capsicum frutescens whole fruits were 4.9 and 110.6 mg GAE/g DW in hexane and acetonitrile extracts, respectively.…”
Section: Polyphenols Contents and Antioxidant Activitiesmentioning
confidence: 99%
“…Aliakbarlu et al [32] found that TPC in red pepper was 34 mg GAE/g DW. Chen and Kang [33] observed that TPC of red peppers in pericarp, placenta and stalk were ranged from 43.3 to 91.9 mg GAE/g DW. Finally, Nascimento et al [34] revealed that total phenolic contents of Capsicum frutescens whole fruits were 4.9 and 110.6 mg GAE/g DW in hexane and acetonitrile extracts, respectively.…”
Section: Polyphenols Contents and Antioxidant Activitiesmentioning
confidence: 99%
“…Chili pepper is one of the vegetable crops having α-glucosidase inhibitory effects [ 24 ]. Previous biochemical analyses showed that pepper leaf and fruit extracts have strong AGI activity [ 25 , 26 ]. However, no reports have examined the inheritance and genetic analysis of AGI activity in pepper.…”
Section: Discussionmentioning
confidence: 99%
“…Several pepper ( Capsicum annuum L.) extracts are reported to have high inhibitory effect on α-glucosidase activity [ 24 ]. An investigation on α-glucosidase inhibitory activity (AGI activity) of various pepper extracts from pericarp, placenta, and stalk showed high inhibitory activity in extracts from pericarp and placenta [ 25 ]. In addition, pepper leaf extracts showed in vitro inhibitory activity of both α-glucosidase and α-amylase [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory activities of the extracts against α-glucosidase were negatively proportional to both TPC and TFC, and the correlation coefficients were R 2 = −0.22, −0.24, at p > 0.05, respectively. Several studies have found a direct correlation between the amount of phenolic compounds in plant extracts and their capacity to inhibit α-enzymes (Patrick et al, 2005;Chen & Kang, 2014). However, not always plant extracts with the high phenolic content have been demonstrated to exert the inhibitory activity on α-amylase (Hairong and Baojun, 2014), which points out the importance of the nature of the different molecules and the interactions among them.…”
Section: Correlation Analysismentioning
confidence: 99%